Surface protein engineering increases the circulation time of a cell membrane-based nanotherapeutic - Krishnamurthy, Sangeetha (2021)
Mammalian cell membranes are often incompatible with chemical modifications typically used to increase circulation half-life. Using cellular nanoghosts as a model, we show that proline-alanine-serine (PAS) peptide sequences expressed on the membrane surface can extend the circulation time of a cell membrane derived nanotherapeutic. Membrane expression of a PAS 40 repeat sequence decreased protein binding and resulted in a 90% decrease in macrophage uptake when compared with non-PASylated controls (P ≤ 0.05). PASylation also extended circulation half-life (t1/2 = 37 h) compared with non-PASylated controls (t1/2 = 10.5 h) (P ≤ 0.005), resulting in ~7-fold higher in vivo serum concentrations at 24 h and 48 h (P ≤ 0.005). Genetically engineered membrane expression of PAS repeats may offer an alternative to PEGylation and provide extended circulation times for cellular membrane-derived nanotherapeutics.